Structure of the convective boundary layer - A method to delineate the sub layers (MAUSAM, 2003)
The paper introduces a different method to delineate the different sub layers in the Convective Boundary Layer over the north Indian Oceanic regions during the summer monsoon season. The all available data set (only aerological observations) from the MONSOON-77 experiment during the June-August 1977 over the Arabian Sea (Phase IA and IB), Equatorial Indian Ocean (Phase II) and Bay of Bengal (Phase III) regions have been considered to demonstrate the usefulness of the above method. The vertical structure of the Convective Boundary Layer revealed the four layered structure viz. surface layer, sub cloud layer, cloud layer and capping stable layer. These layers could be separated from each other by utilizing the averaged vertical profiles of saturation pressure deficit (P*, hPa) and mixing parameter (b, dimensionless). The CBL top is marked by the minimum value of P*.  The study revealed that, in general, the extent of surface and sub cloud layer over the north Indian Oceanic regions is up to 1000 hPa and 950 hPa respectively.  Also, it is observed that the cloud layer depth varies during the phases IA, IB, II and III.  The investigations revealed that  the depth of the CBL is up to 650 hPa during  all the three phases over the ships.